Humour beyond human: eco-humour as a pedagogical toolkit for environmental education - Mohammad Ali Heidari-Shahreza (Australian Journal of Environmental Education)
This article strives to open a window on ‘eco-humour’, an umbrella term for diverse forms of humour targeting ecological and environmental issues. It encourages readers to consider eco-humour as a valuable, pedagogical toolkit for environmental education and communication. To this aim, eco-humour is, first, put into perspective of humour scholarship. In particular, I discuss the critical and corrective potential of humour to address and possibly redress environmental issues. Pedagogical benefits of humour are, then, touched upon to pave the way for a discussion of ‘humour-integrated environmental education’. The paper also addresses UNESCO’s 2030 roadmap of education for sustainable development and the ‘sustainability’ component of Australian Curriculum to further justify and contextualise the use of eco-humour. Moreover, several university-based initiatives to integrate echo-humour into environmental education are considered. Likewise, I briefly address ‘humour-integrated language learning’ as an emerging approach in language education that may offer valuable insights into eco-humour curriculum integration. Finally, the article points out several practical considerations and future directions in humour-integrated environmental education.